Post-transplant Malignancy: An Overview and Review of Literatures - Jebur, Wael Lateef (Journal of Clinical Nephrology, 2025)
Post-transplant malignancy is one of the contentious and feared consequences of Solid Organ Transplantation (SOT), which might detrimentally alter the outcome of transplantation. Risk factors are manifold, principally related to a suppressed immune system with intercurrent immunosuppressant medications commonly used in the context of SOT. Opportunistic viral infections encountered in SOT are crucial promoters of mitogenic proliferation in several common tumors. Lastly, immune suppressant therapy might trigger mitogenic changes directly. In this paper, we are discussing post-SOT malignancies, elaborating on the different phases of its pathogenesis, and elucidating on the different aspects that linger in its risk factors, preventive strategies, and management.